Seniority, External Labor Markets, and Faculty Pay - Byron W. Brown; Stephen A. Woodbury (W.E. Upjohn Institute for Employment Research, 1995)
We estimate the returns to seniority (the wage-tenure profile) for university faculty, and the degree to which these returns respond to entry-level salaries (or opportunity wages) a relationship unexplored in work to date. Using data on faculty at a Big Ten university (ours), we estimate elasticities of senior-faculty salaries with respect to entry-level salaries, and find that these elasticities decline with seniority. The evidence both provides an explanation of faculty salary compression and suggests the importance of controlling for entry-level salaries in obtaining estimates of the returns to seniority.
Keywords: J0; J3; 330; faculty; wages; college; labor; markets; Brown; Woodbury